ENSURING RADIATION SAFETY AT THE XXVII WORLD SUMMER UNIVERSIADE IN KAZAN BY ROSPOTREBNADZOR BODIES AND ORGANIZATIONS Communication 1. Ensuring radiation safety at the preparatory phase - G. G. Onischenko; I. K. Romanovich; M. A. Patyashina; V. B. Ziatdinov; A. A. Gorskiy; V. S. Stepanov; R. K. Ismagilov (Радиационная гигиена, 2015)
After the terrorist attack at theBostonMarathon, Federal and Republican executive bodies took increased security measures during the XXVII World Summer Universiade inKazan. Bodies and Organizations of the Federal Service for Surveillance on Consumer Rights Protection and Human Well-being (Rospotrebnadzor) were participants of all preparatory activities and directly provided security of the Student Games inKazan. This report analyzes the experience of providing radiation safety by Rospotrebnadzor experts at the stage of preparation for the Universiade. So far, Rospotrebnadzor organizations had no experience of providing radiation safety of such large-scale events. Analysis of the performed work with account for both positive and negative experiences is especially important in the context of preparations for the safety providing of the Olympic Winter Games inSochiin 2014.